2023
DOI: 10.3390/metabo13020227
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Signatures Elucidate the Effect of Body Mass Index on Type 2 Diabetes

Abstract: Obesity plays an important role in the development of insulin resistance and diabetes, but the molecular mechanism that links obesity and diabetes is still not completely understood. Here, we used 146 targeted metabolomic profiles from the German KORA FF4 cohort consisting of 1715 participants and associated them with obesity and type 2 diabetes. In the basic model, 83 and 51 metabolites were significantly associated with body mass index (BMI) and T2D, respectively. Those metabolites are branched-chain amino a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 84 publications
0
8
0
Order By: Relevance
“…Another related study also proved that BMI had a direct causal relationship with T2DM, and found that weight control and blood lipid control played an important role in preventing diabetes [29]. The research results of Qiuling Dong et al clari ed the causal relationship between BMI and T2DM from the perspective of metabolic characteristics, and provided new ideas and directions for treatment strategies related to diabetes [30].…”
Section: Discussionmentioning
confidence: 95%
“…Another related study also proved that BMI had a direct causal relationship with T2DM, and found that weight control and blood lipid control played an important role in preventing diabetes [29]. The research results of Qiuling Dong et al clari ed the causal relationship between BMI and T2DM from the perspective of metabolic characteristics, and provided new ideas and directions for treatment strategies related to diabetes [30].…”
Section: Discussionmentioning
confidence: 95%
“…Other lipids, as sphingolipid C16:1 SM, were also included in the legume-related-metabolite signature and showed a decreased risk association for T2D. Biological pathway analysis in combination with genetics and mice experiments indicates that the downregulation or upregulation of sphingolipid is a causal factor in early-stage T2D pathophysiology and is associated with a decreased risk of T2D [ 55 , 56 ]. The positive association between C7 and C18:2 acylcarnitines and legume consumption could be an indirect reflection of high fish consumption by those individuals allocated in the highest tertile of legume consumption, as fish has been established as one of the main dietary sources of acylcarnitines, although no association between short chain acylcarnitines and diabetes risk has been previously reported [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…during which analytical procedures have been upgraded several times 26 . The targeted metabolomics data of F4 were measured with the analytical kit AbsoluteIDQ ® p150 42,43 , while S4 and FF4 data were quantified using the kit AbsoluteIDQ ® p180 [44][45][46] (Biocrates Life Sciences AG, Innsbruck, Austria). To assess the technical variation introduced by different kits, samples from 288 individuals from the F4 were remeasured (September-October 2019) using the p180 kit.…”
Section: Mgh Covid Datasetmentioning
confidence: 99%